2021
DOI: 10.1002/tsm2.293
|View full text |Cite
|
Sign up to set email alerts
|

Different training responses in elderly men and women following a prolonged muscle resistance training intervention

Abstract: Resistance training is an effective strategy to counteract the age‐related loss of muscle mass and strength in elderly, but whether the benefits of training differ between sexes is unclear. A total of 297 elderly men and women were randomized to 1 year of heavy resistance training (HRT) or control (CON). Changes in muscle function and body composition were compared between sexes and groups. Improvements in muscle strength, body fat, muscle mass and size were observed, but the absolute improvements in muscle st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a 2016 study of sex differences in responses to RE training in 23 older persons aged 65 years, isometric knee extensor strength increased by 41.7% in men and 15.8% in women after RE [14]. A study, published in 2021 by Anne et al [45], of 275 older people (aged 62-70 years) investigated sex differences in responses to gradual RE three times a week for 9 weeks showed an increase in maximal isometric knee extensor strength of 26 Nm in men and 10 Nm in women. A study published in 2000-year investigating the effect of RE on muscle quality according to sex and age in 22 older people (aged 65-75 years) showed that knee extensor strength (1RM) improved by 19.9 kg in men and 12.2 kg in women after RE investigating the effect of RE on muscle quality according to sex and age in 22 older people (aged 65-75 years) showed that knee extensor strength (1RM) improved by 19.9 kg in men and 12.2 kg in women after RE [46].…”
Section: Sex Differences In Muscle Strength and Re Adaptation In Olde...mentioning
confidence: 99%
See 4 more Smart Citations
“…In a 2016 study of sex differences in responses to RE training in 23 older persons aged 65 years, isometric knee extensor strength increased by 41.7% in men and 15.8% in women after RE [14]. A study, published in 2021 by Anne et al [45], of 275 older people (aged 62-70 years) investigated sex differences in responses to gradual RE three times a week for 9 weeks showed an increase in maximal isometric knee extensor strength of 26 Nm in men and 10 Nm in women. A study published in 2000-year investigating the effect of RE on muscle quality according to sex and age in 22 older people (aged 65-75 years) showed that knee extensor strength (1RM) improved by 19.9 kg in men and 12.2 kg in women after RE investigating the effect of RE on muscle quality according to sex and age in 22 older people (aged 65-75 years) showed that knee extensor strength (1RM) improved by 19.9 kg in men and 12.2 kg in women after RE [46].…”
Section: Sex Differences In Muscle Strength and Re Adaptation In Olde...mentioning
confidence: 99%
“…In several studies examining the effect of RE according to sex differences in older individuals, men showed higher muscle strength improvement than did women [14,[43][44][45][46]. In a s tudy published in 2021-year examined sex differences in response to RE over a 40-week period in 160 older adults (aged 55-74 years).…”
Section: Sex Differences In Muscle Strength and Re Adaptation In Olde...mentioning
confidence: 99%
See 3 more Smart Citations